LOW TEMPERATURE SYNTHESIS OF DENSE REACTION-BONDED-MULLITE VIA TRANSIENT LIQUID - HanSoo, Kim (My University, 2001)
A near-net-shape process for the production of mullite matrix ceramic composites below 1300 °C has been achieved by reaction bonding AI2O3, silicon, mullite seeds and a eutectic of A12O3-SiO2-mixed rare earth oxide. The roles of the transient liquid phase from the eutectic and the mullite seeds are examined. The approximate eutectic composition was estimated from the A12O3-SiO2-Y2O3 phase diagram as 22 wt % AI2O3/46 wt% S102/3 2 wt% Y2O3. The fusion temperature of the mixed-rare-earth-based eutectic composition was lower (1175 °C vs. those of pure, rare earth oxides based eutectic composition; Pr6On/A12O3/SiO2: 1224 °C, EU2O3/AI2O3/S1O2: 1259 °C and Y2O3/Al2O3/SiO2: 1345 °C). The densification characteristics of the reaction-bonded mullite (RBM) mixture were investigated. Density increased with eutectic, and decreased with mullite seed contents. Oxidation and volume expansions due to Si and mullite formation are examined by thermogravimetric analysis (TGA) and dilatometric measurement. TThe measured weight gain and maximum volume expansion were lower than theoretical values due to preoxidation of the Si powder. Dilatometric curves indicated sintering shrinkage is compensated by the oxidation-induced volume-expansion. AI2O3 + SiO2 mixtures of the mullite composition exhibited shrinkage exclusively. X-ray diffraction of the RBM sinters display major mullite peaks and minor residual a-A12O3. Mullite develops with low residual AI2O3 when 7.5 wt% mixed-rare-earth-oxide eutectic and 5 wt% mullite seeds are incorporated into the mix. The final sinter is > 90 % theoretical density, > 90 % mullite, and suffers 2.2 % sintering shrinkage. Transmission-electron-microscopy (TEM) and Energy dispersive X-ray spectra (EDX) were employed to follow mullite evolution. Model samples were utilised to study diffusion-, and reaction-, rates. The highest reaction rates at the lowest temperature occur when the eutectic penetrates an AI2O3/S1 layer. Bimodal pellets with and without eutectic (or with and without mullite seeds) directly illustrate their roles. Mullite seeds promote mullite formation, but the transient liquid accelerates Si oxidation, mullite formation and densification.
Keywords: low-temperature synthesis; Dense Reaction- Bonded-Mullite via Transient Liquid